Social Impact Assessment of Crude Oil Pollution on Small Scale Farmers in Oil Producing Communities of the Central Agricultural Zone of Delta State, Nigeria - A. O. U., Ofuoku; F. N, Emuh; O, Ezeonu (Asian Journal of Agriculture and Rural Development, 2014)
The study assessed the social impact of oil production on small holder farmers in oil-producing communities of the Central zone of Delta State, Nigeria. Data were collected from 120 respondents by the use of questionnaires. Soil erosion (96.6%), noise pollution (98.3%), bush burning (93.3%), land degradation/pollution (87.5%), water pollution (80.3%), air pollution (62.5%), massive deforestation (62.5%) and acid rain (52.5%) were seen as the major environmental problems experienced in the study area. The respondents reported that oil pollution impacted negatively on their income (83.3%), agricultural production (98.3%) and land availability (85.8%). None of the socio-economic characteristics of the respondents such as age, gender, Educational level, religion, marital status, type of farming, family size, Farming experience, farm size, income, housing, tenure, membership of organization, land tenure and source of labour were found to determine the social impact of oil pollution on small-scale farmers. Recommendations given dwelt on making the environment conducive for the communities, agricultural activities and it sustenance for future generations.